1997
DOI: 10.1080/014311697217819
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of AVHRR/NDVI-ecoclimatological relations in Nebraska, U.S.A.

Abstract: Research designed to better de® ne relations between 1-km multitemporal AVHRR-derived NDVI data and selected climatological parameters, soil hydrological properties and land cover characteristics is summarized. Bi-weekly maximum value composite NDVI data and concurrently measured meteorological data acquired in 1990 and 1991 for Nebraska were utilized to study relations between NDVI and accumulated growing degree days, soil temperature, precipitation and potential evapotranspiration. Temporal change in NDVI wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 23 publications
5
77
0
4
Order By: Relevance
“…A very weak negative correlation was found at the end (late fall and winter) and the beginning of the growing season (part of the spring months). Previous studies have concluded that temporal variations of NDVI are closely related to precipitation and a strong linear relationship between NDVI and precipitation exits on regional [47][48][49][50][51][52] and global scales [53]. Wang et al [47] observed that NDVI curves and precipitation curves are parallel, displaying an increasing trend during warm months and a decreasing pattern in cold months.…”
Section: Climatic Influences On Ndvimentioning
confidence: 99%
“…A very weak negative correlation was found at the end (late fall and winter) and the beginning of the growing season (part of the spring months). Previous studies have concluded that temporal variations of NDVI are closely related to precipitation and a strong linear relationship between NDVI and precipitation exits on regional [47][48][49][50][51][52] and global scales [53]. Wang et al [47] observed that NDVI curves and precipitation curves are parallel, displaying an increasing trend during warm months and a decreasing pattern in cold months.…”
Section: Climatic Influences On Ndvimentioning
confidence: 99%
“…Dealing with the remotesensing-climate relationship, the influence of climatic conditions on vegetation growth, and its impacts on NDVI, are often indirect. Specific interpretation of observed variations in NDVI is not well documented in terms of interactions among vegetation, climate and soil (Yang et al, 1997). Last but not least, the mechanism of the phenology-remote-sensing relationship is relatively clear, because NDVI derived from satellite measurements can be conceptually described as a function of visible and near-infrared reflectance from the plant canopy, soil, and atmosphere, in which plants play an essential role.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, several authors have developed procedures to determine satellite sensor-derived growing season using normalized difference vegetation index (NDVI) data for a single pixel (Reed et al, 1994;White et al, 1997) or for large spatial scales (Myneni et al, 1997;Zhou et al, 2001). Other authors have used the onset and end of greenness and time-integrated (TI) NDVI as surrogates for growing season and primary production, and established statistical relationships between NDVI or TI NDVI and climate variables for gauging and monitoring vegetation dynamics (Yang W. et al, 1997;Yang L. et al, 1998;Fu and Wen, 1999). However, because NDVI metrics and thresholds may not directly correspond to conventional, ground-based phenological events, but rather provide indicators of vegetation dynamics (Justice et al, 1986;Lloyd, 1990), a detailed comparison of these satellite measures with ground-based phenological events is needed (Reed et al, 1994;Schwartz and Reed, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the phenological events in this study are determined by satellite data only. the spring events were increasingly occurring earlier in the recent decades [2,4,8,13,16,19,23] . This study estimated that the onset date of the green up of the selected zone of Iran advanced on average by 0.63 days year −1 from 1982-1999.…”
Section: Discussionmentioning
confidence: 99%